Recent advances in heteroatom-doped RuO2 electrocatalysts for efficient acidic oxygen evolution reaction - Yihao Zheng; Tao Zhou; Quan Zhang; Haixin Guo; Jianxun Yang; Baofu Ding; Huaiyu Shao; Xinchun Yang (Science and Technology of Advanced Materials, 2025)
Highly active and durable acidic oxygen evolution reaction (OER) electrocatalyst is a vital component of cost-effective proton exchange membrane water electrolyzer. Rutile-phase RuO2 has inspired extensive attention as an acidic OER electrocatalyst due to its lower cost and similar activity compared to IrO2. However, RuO2 often suffers from severe dissolution and even structural collapse at high potentials due to the irreversible overoxidation of Ru into soluble RuO4 species, resulting in a dramatic degradation of performance. Thus, suppressing Ru dissolution and improving intrinsic activity are crucial challenges in the design of RuO2-based electrocatalysts. Extensive efforts have proven that incorporating foreign metal/non-metal dopants into RuO2 is an extremely practical and effective strategy for boosting RuO2. In this review, an overview of mechanisms of acidic OER and classification of the doping forms is first provided. Subsequently, a comprehensive review of RuO2-based electrocatalysts with various doping types is presented, along with the underlying mechanisms that facilitate breaking the trade-off between activity and stability. Finally, our insights into current challenges and future research trends are proposed for developing robust RuO2-based electrocatalysts toward acidic OER.